Frustrated ambition General Vicente Lim and the Philippine Military Experience, 1910-1944 - Meixsel, Richard B. 1955- (Campaigns and commanders, 2018)
"Uses the career of Vicente Lim, the first Filipino graduate of West Point and commanding general of a Philippine Army division on Bataan during World War II, to reappraise the military history of both the Commonwealth-era Philippine Army (1936-1942) and the Philippines during the American period of occupation"--